Estimate the conservation value of biodiversity in national heritage site: a case of Forest Research Institute Malaysia - Abdullah, Mukrimah; Mamat, Mohd Parid; Yaacob, Mohd Rusli; Radam, Alias; Lim, Hin Fui (Elsevier, 2015)
Forest Research Institute Malaysia (FRIM) offers a variety of forest ecosystem services such as biodiversity conservation, recreation, ecotourism and nature-environmental education. These services are limited in supply and may lead to the reduction if resources are not managed and conserved well. Conservation of biodiversity is one of the efforts to ensure sustainability of biodiversity. The study was conducted in 2014 to value willingness to pay (WTP) for conserving biodiversity at FRIM among residents of Selangor. This study found the mean WTP ranges from RM53.24 to RM67.22, which could contribute annual revenue ranged from RM66.3 million to RM83.8 million.